One Last Puff? Public Smoking Bans and Smoking Behavior - Silke Anger; Michael Kvasnicka; Thomas Siedler (Journal of Health Economics, 2011)
This paper investigates the short-term effects of public smoking bans on individual smoking behavior. In 2007 and 2008, state-level smoking bans were gradually introduced in all of Germany's federal states. We exploit this variation to identify the effect that smoke-free policies had on individuals' smoking propensity and smoking intensity. Using rich longitudinal data from the German Socio-Economic Panel Study, our difference-in-differences estimates show that the introduction of smoke-free legislation in Germany did not change average smoking behavior within the population. However, our estimates point to important heterogeneous effects. Individuals who go out more often to bars and restaurants did adjust their smoking behavior. Following the ban, they became less likely to smoke and also smoked less.
Additional information: NOTICE: This is the author's version of a work that was accepted for publication in Journal of Health Economics. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Journal of Health Economics 30 (2011), 3, pp. 591-601 and is online available at http://dx.doi.org/10.1016/j.jhealeco.2011.03.003.
Keywords: I12; K32; I18; C33; 330; Public smoking bans; Smoking; Cigarette consumption; Treatment effects; Rauchen; Konsumentenverhalten; Deutschland